Identification of inelastic parameters of the AISI 304 stainless steel - Vaz M.* (2020)
© Springer Nature Switzerland AG 2020.A proper choice of inelastic parameters is one of the most important aspects for a successful simulation of metal forming processes. Several issues must be observed when choosing such parameters, amongst which the compatibility between the magnitude of the plastic deformation of the target forming operation and the mechanical test employed to obtain those parameters. Within this context, the present work addresses the suitability of selected phenomenological hardening models and identification of the corresponding inelastic parameters based on curve-fitting strategies (logarithmic-based equations) and optimization methods (non-logarithmic models) for the AISI 304 austenitic stainless steel. Tensile tests were performed using specimens of different sizes. Based on a combined assessment of all types of specimens, it was observed that the curve-fitting technique was able to describe with excellent accuracy deformations up to maximum load. In order to contemplate larger plastic deformations, an inverse problem strategy based on optimization methods was used to account for material response up to macroscopic failure of the specimens. Numerical simulation of the tensile tests shows that the latter technique associated with non-logarithmic hardening equations provided the best approximation to the experimental data.